Wittgenstein and modernist fiction : the language of acknowledgment - Chase, Greg (Anthem studies in Wittgenstein., 2022)
"Wittgenstein and Modernist Fiction: The Language of Acknowledgment shows how early twentieth-century economic and social upheaval prompted new ways of conceptualizing the purposes and powers of language. Scholars have long held that formally experimental novels written in the early twentieth century reflect how the period's material crises--from world wars to the spread of industrial capitalism--call into question the capacity of language to picture the world accurately. This book argues that this standard scholarly narrative tells only a partial story. Even as signal modernist works by Virginia Woolf, Nella Larsen, William Faulkner, and others move away from a view of language as a means of gaining knowledge, they also underscore its capacity to grant acknowledgment. They show how language might matter less as a medium for representing reality than as a tool for recognizing others."--